Factors Affecting the Counterproductive Behaviors of Employees in the Organization; Emphasizing the Role of Organizational Embeddedness, Emotional Intelligence and Psychological Ownership - Marziyeh Dehghanizadeh; Mehdi Kheirandish; Hojjat Kheirandish (مدیریت بهره وری)
Abstract: The present study sought to investigate factors affecting the counterproductive employee behaviors in the organization, emphasizing the role of organizational embeddedness, emotional intelligence and psychological ownership in Isfahan Oil Products Distribution Company. It is practical in terms of purpose and descriptive-survey in terms of data collection. The statistical population of the present study was the staff of Isfahan Oil Products Distribution Company (300 people), from which 168 participants were recruited through simple random sampling. The instruments for collecting data in this research were standard questionnaires, and the analysis used was the structural equation modeling technique. The findings of the research showed that organizational justice had a negative significant effect on counterproductive behaviors directly and also through the mediating variable of organizational embeddedness. Also, the effect of organizational justice on organizational embeddedness and the effect of organizational embeddedness on counterproductive behaviors were confirmed. Finally, it was found that, psychological ownership had a moderating role in the relationship between organizational embeddedness and counterproductive behaviors; however, emotional intelligence did not have a moderating role in the relationship between organizational justice and counterproductive behaviors. Therefore, according to the resource conservation theory, organizational embeddedness is considered as a state of resource abundance, and psychological ownership directly affects the value and importance of the available resources; therefore, organizational embeddedness and psychological ownership are important factors in predicting the impact of contextual variables such as organizational justice on employee behavior such as counterproductive behaviors. Organizational justice creates a favorable environment for employees to acquire resources. Also, managers should pay attention to the fact that employees with high emotional intelligence may be less prone to counterproductive behaviors. Key Words: organizational justice, counterproductive behaviors, organizational embeddedness, psychological ownership, emotional intelligence. 1.Introduction Today, one of the deviant behaviors observed in both public and private organizations is counterproductive behaviors, the consequences of which are hostile for employees, shareholders, organizations, communities, and even nations. Therefore, researchers are interested in identifying the determinants of counterproductive work behaviors to minimize their occurrence (Spencer et al., 2020). Previous studies have shown that counterproductive work behaviors are influenced by several factors. One of these factors is organizational justice, and researches have shown that organizational justice is a basic and important predictor in organizations (Patnaik et al., 2023). Also, in this regard, the conservation of resources perspective is both important and relevant, yet, it has been somewhat overlooked in contemporary research on counterproductive work behavior (Hobfoll et al., 2018). To fill this gap, the present study uses the resource conservation perspective to identify a mediator (organizational embeddedness) and moderator (psychological ownership) derived from this perspective, which has not previously been studied in research on counterproductive work behaviors. Also, in this research, the moderating effect of emotional intelligence has been considered in the relationship between organizational justice and counterproductive behaviors. Therefore, the purpose of this study is to investigate factors affecting the counterproductive behaviors of employees in the organization, emphasizing the role of organizational embeddedness, emotional intelligence and psychological ownership in Isfahan Oil Products Distribution Company. Literature Review Counterproductive work behaviors are intentional actions that harm the organization or its members (Carpenter et al., 2021). Zhao et al. (2013) warned that counterproductive work behaviors are more common than other negative employee behaviors, and that workplace behaviors involve all voluntary behaviors that conflict with organizational values, norms, and legitimate interests, and are harmful to the organization, employees, and stakeholders. Badawy (2023) examined how emotional intelligence moderates the relationship between perceived justice and counterproductive behaviors. Hence, the purpose of this study is to demonstrate the power of emotional intelligence in curbing employees' negative reactions to perceived organizational injustice, which manifests in counterproductive behaviors. The results support the moderating effect of emotional intelligence for counterproductive behaviors in general and counterproductive behaviors directed toward individuals in particular. As expected, individuals with high emotional intelligence were less likely to engage in counterproductive behaviors, even in the presence of perceived injustice, and individuals with moderate levels of emotional intelligence were more likely to engage in counterproductive behaviors when compared to individuals with low emotional intelligence when they perceived injustice. Tziner et al. (2020) conducted a study entitled “combining associations between emotional intelligence, work motivation, and organizational justice with counterproductive work behavior”. The results showed that high justice and low emotional intelligence and high emotional intelligence and low work motivation are related to interpersonal deviance and organizational deviance as well as emotional exhaustion and job satisfaction. Hence, the purpose of this study is to demonstrate the power of emotional intelligence in curbing employees' negative reactions to perceived organizational injustice, which manifests in counterproductive behaviors. Methodology The current study is practical in terms of purpose and descriptive-survey in terms of data collection. The statistical population of the present study was the staff of Isfahan Oil Products Distribution Company (300 people), from which 168 participants were selected through simple random sampling. The data collection instruments in this research were standard questionnaires, including the organizational justice questionnaire of Kim et al. (2021) and Niehoff and Moorman (1993); the counterproductive work behavior questionnaire of Fox et al. (2001) and Maclane and Walmsley (2010); the organizational embeddedness questionnaire of Tian et al. (2016); the psychological ownership questionnaire of Van Dyne and Pierce (2004); and the emotional intelligence questionnaire of Wong and Low (2002). The validity of the questionnaires was confirmed a panel of experts in the field, and Cronbach's alpha coefficient and composite reliability were used to estimate the reliability of the instruments. The analysis method used in this research was the structural equation modeling technique. Result The findings of the research showed that organizational justice had a negative significant effect on counterproductive behaviors directly and also through the mediating variable of organizational embeddedness; also, the effect of organizational justice on organizational embeddedness and the effect of organizational embeddedness on counterproductive behaviors were confirmed. Finally, it was found that, psychological ownership had a moderating role in the relationship between organizational embeddedness and counterproductive behaviors, but emotional intelligence did not have a moderating role in the relationship between organizational justice and counterproductive behaviors. Discusion According to the resource conservation theory, organizational embeddedness is considered as a state of resource abundance, and employees consider organizational embeddedness as a valuable resource that must be accumulated and protected. Moreover, psychological ownership directly affects both the value and importance of available resources and these factors are such that managers can influence them through various interventions. Therefore, organizational embeddedness and psychological ownership are important factors in predicting the impact of contextual variables such as organizational justice on employee behavior such as counterproductive behaviors and organizational justice can create a favorable environment for employees to acquire resources. Additionally, managers should pay attention to the fact that employees with high emotional intelligence may be less prone to counterproductive behaviors.